Risk Factors for Development of Biliary Stricture in Patients Presenting with Bile Leak after Cholecystectomy - Lokesh, Hosur Mayanna (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Pancreatobiliary Association; Korean Society of Gastrointestinal Cancer, 2013)
BACKGROUND/AIMS: This study was aimed at determining the factors associated with the development of benign biliary stricture (BBS) in patients who had sustained a bile duct injury (BDI) at cholecystectomy and developed bile leaks. METHODS: A retrospective analysis of 214 patients with BDI who were referred to our center between January 1989 and December 2009 was done. RESULTS: One hundred fifty-three (71%) patients developed BBS (group I), and 61 (29%) were normal (group II). By univariate analysis, female gender (p=0.02), open cholecystectomy as the index operation (p=0.0001), delay in the referral from identification of injury (p=0.04), persistence of an external biliary fistula (EBF) beyond 4 weeks (p=0.0001), EBF output >400 mL (p=0.01), presence of jaundice (p=0.0001), raised serum total bilirubin level (p=0.0001), raised serum alkaline phosphatase level (p=0.0001), and complete BDI (p=0.0001) were associated with the development of BBS. Furthermore, open cholecystectomy as the index operation (p=0.04), delayed referral (p=0.02), persistent EBF (p=0.03), and complete BDI (p=0.001) were found to predict patient outcome in the multivariate analysis. CONCLUSIONS: For the majority of patients with BDI, the risk of developing BBS could have been predicted at the initial presentation.